2014
DOI: 10.1371/journal.pgen.1004636
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally-Regulated Excision of the SPβ Prophage Reconstitutes a Gene Required for Spore Envelope Maturation in Bacillus subtilis

Abstract: Temperate phages infect bacteria by injecting their DNA into bacterial cells, where it becomes incorporated into the host genome as a prophage. In the genome of Bacillus subtilis 168, an active prophage, SPβ, is inserted into a polysaccharide synthesis gene, spsM. Here, we show that a rearrangement occurs during sporulation to reconstitute a functional composite spsM gene by precise excision of SPβ from the chromosome. SPβ excision requires a putative site-specific recombinase, SprA, and an accessory protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(157 citation statements)
references
References 52 publications
7
148
0
Order By: Relevance
“…Normally, the excision of the SPβ prophage from the B. subtilis chromosome takes place before sporulation and allows reconstitution of the spsM gene involved in spore polysaccharide biosynthesis42. Sanchez-Vizuete et al 43.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the excision of the SPβ prophage from the B. subtilis chromosome takes place before sporulation and allows reconstitution of the spsM gene involved in spore polysaccharide biosynthesis42. Sanchez-Vizuete et al 43.…”
Section: Discussionmentioning
confidence: 99%
“…These carbohydrates display structural similarity to those of the B. cereus family spores (49,50). Production and/or attachment of polysaccharides to the B. subtilis spore surface was shown to be spsM dependent (51). This determinant is the site of SP␤ prophage integration, and functional SpsM is produced only following excision of the prophage during sporulation (51).…”
Section: The Spore Crust Layermentioning
confidence: 99%
“…Production and/or attachment of polysaccharides to the B. subtilis spore surface was shown to be spsM dependent (51). This determinant is the site of SP␤ prophage integration, and functional SpsM is produced only following excision of the prophage during sporulation (51). Spores from spsM- negative mutants had altered surface properties, including increased adherence to glass and enhanced aggregation in aqueous environments.…”
Section: The Spore Crust Layermentioning
confidence: 99%
“…Recent work showed that the site-specific recombination of the SP␤ region also occurs during sporulation, which generates the functional spore polysaccharide gene spsM from truncated yodU and ypqP (43). The sequences that ResD and NsrR bind cover the sites of recombination catalyzed by recombinases SprA (for SP␤) (43) and SpoIVCA (for sigK) (39) (Data Set S1). ResD and NsrR bind to the upstream site of ypqP that encodes the C-terminal part of SpsM (see Fig.…”
Section: Figmentioning
confidence: 99%